Microstructural organization of the corpus callosum in young endurance athletes: A global tractography study - Tarumi, Takashi; Fukuie, Marina; Yamabe, Takayuki; Kimura, Ryota; Zhu, David C.; Ohyama-Byun, Keigo; Maeda, Seiji; Sugawara, Jun (Frontiers in Neuroscience, 2022)
Introduction Aerobic exercise training has been shown to improve microstructural organization of the corpus callosum (CC); however, evidence of this topographic effect is limited. Purpose To compare the CC microstructural organization between endurance athletes and sedentary adults using a white-matter fiber tractography approach. Materials and methods Diffusion tensor imaging (DTI) and T1-weighted structural data were collected from 15 male young endurance athletes and 16 age- and sex-matched sedentary adults. DTI data were analyzed with a global probabilistic tractography method based on neighborhood anatomical information. Fractional anisotropy (FA) and mean, radial (RD), and axial diffusivities were measured in the eight CC tracts: rostrum, genu, splenium, and body’s prefrontal, premotor, central, parietal, and temporal tracts. Cortical thickness of the CC tract endpoints and the CC tract length and volume were also measured. Physical activity level was assessed by metabolic equivalents (METs). Results The athlete group had an average VO2max of 69.5 ± 3.1 ml/kg/min, which is above 90%ile according to the American College of Sports Medicine guideline. Compared with the sedentary group, the athlete group had higher FA in the CC body’s premotor and parietal tracts and the CC splenium. These tracts showed lower RD in the athlete compared with sedentary group. The voxelwise analysis confirmed that the athlete group had higher FA in the CC and other white matter regions than the sedentary group, including the corona radiata, internal capsule, and superior longitudinal fasciculus. Cortical thickness of the CC tract endpoints and the CC tract lengths and volumes were similar between the two groups. Physical activity levels were positively correlated with FA in the CC body’s parietal (r = 0.486, p = 0.006) and temporal (r = 0.425, p = 0.017) tracts and the CC splenium (r = 0.408, p = 0.023). Conclusion Young endurance athletes have higher microstructural organization of the CC tracts connected the sensorimotor and visual cortices than the age- and sex-matched sedentary adults.